The Role of School Administrators in Promoting Learning Management in the Digital Age under Nakhon Si Thammarat Primary Educational Service Area Office 1 - Sukanan, Wilasinee; Wannapairo, Suntaree (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
This research aims to 1) examine the role of school administrators in promoting learning management in the digital, 2) compare the role of school administrators in promoting learning management in the digital, categorized by gender, age, school size, educational qualifications, and work experience, and 3) explore guidelines for developing the role of school administrators in promoting learning management in the digital. Data were collected through questionnaires completed by teachers and interviews with school administrators. The research findings indicated that: 1) the role of school administrators in promoting learning management in the digital was at a high level, 2) the comparison of the role of school administrators in promoting learning management in the digital by gender, age, and educational qualifications revealed no significant differences in perspectives. However, significant differences at the .01 level were observed in perspectives based on work experience and school size; and 3) the guidelines for enhancing the role of school administrators in promoting learning management in the digital suggested that school administrators should allow teachers and staff to participate in defining visions and policies focused on digital learning, prioritize technology and modern media, conduct supervision, follow-up, and assess learning outcomes, and support online data storage and the use of ready-made programs for convenience and accuracy in evaluation processes.